40 years of ZFN – the flexibility of youth and the experience of age - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
Various anniversaries encourage historical reflection. Although 40th anniversary is not a common reason for excessive celebration, in the case of a scientific journal, however, it is already long enough that it deserves a brief moment of thought.
Keywords: Zagadnienia Filozoficzne w Nauce; Philosophical Problems in Science